THE ROLE OF BVAS IN SAFEGUARDING ELECTORAL INTEGRITY: AN EVALUATION OF THE 2023 GENERAL ELECTIONS IN FCT, ABUJA - Ogbadebo, Adedeji (Journal of Social Political Sciences, 2025)
The Bimodal Voter Accreditation System (BVAS) was introduced in Nigeria to address election malpractices and enhance electoral integrity. This study evaluates the effectiveness of BVAS in safeguarding the 2023 general elections in Nigeria’s Federal Capital Territory (FCT), Abuja, focusing on its role in reducing fraud and improving transparency. A quantitative research design was employed, utilizing online questionnaires to gather data from 385 respondents. Key findings reveal that BVAS significantly reduced voter impersonation and multiple voting, with 85.7% of respondents affirming its efficacy in curbing electoral fraud. However, challenges such as inadequate infrastructure, insufficient technical training for election officials, and low voter awareness hindered optimal performance. Binary logit regression analysis identified voter education, infrastructural development, and funding as critical determinants of BVAS success. While the majority of respondents acknowledged BVAS’s contribution to transparency and fraud reduction, persistent technical and systemic barriers underscore the need for further refinements. The study concludes that BVAS holds promise for improving electoral credibility, but its full potential requires comprehensive voter education programs, robust infrastructural investments, and enhanced public awareness campaigns. Recommendations include targeted training for election personnel, technological upgrades, and policy reforms to address existing gaps. These measures are essential to maximize BVAS’s impact and ensure sustainable electoral integrity in Nigeria.